Evidência de helicobacter spp. em gatos domésticos necropsiados na região central do Rio Grande do Sul - Galindo, Victor Reis (2022)
Helicobacter spp. are spiral-shaped, gram negative, microaerophilic bacteria that colonizes stomach and intestines of humans and various other animals, such as dogs and cats. Helicobacter pylori is the most studied species and its colonization is associated to gastritis, peptic ulcers and gastric carcinoma in humans, however it was already identified on bile from cats. H. salomonis, H. bizzozeronii, H. felis and H. heilmannii species are known as Non-H. pylori Helicobacter (NHPH), and they had highest rates of isolation from gastric mucosa from dogs and cats, nevertheless they were found on human beings also. According to case reports dogs and cats may act as a source of infection to humans, part of it is due to licking habbit from these animals as affection demonstration and because of grooming. In this context, this study aims to trace an epidemiologic profile and determine the most prevalent gender of these bacteria in cats from central State of Rio Grande do Sul, correlationate the presence of bacteria on stomach, liver and bile with urease rapid test and gastric and hepatic histopathologic changes. Therefore, this study used 30 necropsied cats, samples from gastric body and piloric antrum were submitted to urease rapid test (URT) to verify bacteria presence or absence, histopathology (stomach and liver) to observe tissue alterations, and PCR (stomach, liver and bile) to Helicobacter spp. phylogenetic analysis and genome sequencing. It was found that a total of 60% (18/30) of animals were positive on URT from gastric body, and 50% (15/30) were positive on pyloric antrum. Within 15 patients, 10 were male cats (70%), thus positive results were associated to male gender. It was observed mild histopathologic changes on majority of gastric and hepatic samples. Gastric samples subjected to PCR were positive on 60,7% (17/28), hepatic samples on 17,8% (5/18) and bile samples on 3,5% (1/28). The samples exhibited high nucleotide identity with NHPH species.